2009
DOI: 10.1073/pnas.0901867106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tension contributes to clustering of neurotransmitter vesicles at presynaptic terminals

Abstract: Memory and learning in animals are mediated by neurotransmitters that are released from vesicles clustered at the synapse. As a synapse is used more frequently, its neurotransmission efficiency increases, partly because of increased vesicle clustering in the presynaptic neuron. Vesicle clustering has been believed to result primarily from biochemical signaling processes that require the connectivity of the presynaptic terminal with the cell body, the central nervous system, and the postsynaptic cell. Our in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 43 publications
6
145
1
1
Order By: Relevance
“…In the second approach, forces are applied directly to the axon by pulling on the growth cone. Using glass needles, this latter approach has been used to model formation of new axon (Bernal, Pullarkat et al 2007; O'Toole, Lamoureux et al 2008;Lamoureux, Heidemann et al 2010), to identify force thresholds for elongation and retraction (Dennerll, Lamoureux et al 1989;Zheng, Lamoureux et al 1991;Lamoureux, Zheng et al 1992), and to analyze neurotransmitter clustering in axon terminals (Siechen, Yang et al 2009). A unique tissue engineering extension of this method was developed to produce large nerve constructs using an automated Axon Stretch Growth (ASG) bioreactor system (Iwata, Browne et al 2006;Pfister, Iwata et al 2006).…”
Section: Overview Of the Axon Stretch Growth Bioreactor Systemmentioning
confidence: 99%
“…In the second approach, forces are applied directly to the axon by pulling on the growth cone. Using glass needles, this latter approach has been used to model formation of new axon (Bernal, Pullarkat et al 2007; O'Toole, Lamoureux et al 2008;Lamoureux, Heidemann et al 2010), to identify force thresholds for elongation and retraction (Dennerll, Lamoureux et al 1989;Zheng, Lamoureux et al 1991;Lamoureux, Zheng et al 1992), and to analyze neurotransmitter clustering in axon terminals (Siechen, Yang et al 2009). A unique tissue engineering extension of this method was developed to produce large nerve constructs using an automated Axon Stretch Growth (ASG) bioreactor system (Iwata, Browne et al 2006;Pfister, Iwata et al 2006).…”
Section: Overview Of the Axon Stretch Growth Bioreactor Systemmentioning
confidence: 99%
“…84 Siechen and co-workers found that vesicle clustering at the neuromuscular presynaptic terminals of embryonic Drosphila depended on the mechanical tension in the axons. 6 In severed axons which are slack, vesicle clustering was absent; however, vesicle clustering was restored with the application of mechanical tension to the severed end of the axon. Vesicle clustering was also observably increased when mechanical tension was applied to axons indirectly via the post-synaptic muscle.…”
Section: Regulation Of Synapses and Neurotransmitter Releasementioning
confidence: 99%
“…The partial derivative of is shown in Equation 6 by knowing that during magnetic ratcheting, is kept constant and using the substitution = ̅ . The can thus be numerically represented in Equation 7.…”
Section: Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments by Siechen et al (2009) introduced a novel, unexpected jigsaw piece to this scene. In an innovative study, the authors demonstrated that the mechanical tension within axons is essential for effective vesicle clustering in the presynaptic terminal.…”
mentioning
confidence: 99%